2019
DOI: 10.2174/0929867324666171006132729
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Degrading Enzymes and their Application in Cancer Therapy

Abstract: Amino acids are essential components in various biochemical pathways. The deprivation of certain amino acids is an antimetabolite strategy for the treatment of amino acid-dependent cancers which exploits the compromised metabolism of malignant cells. This review summarizes recent progress in the relationship between amino acids metabolism and cancer therapy, with a particular focus on L-asparagine, L-methionine, L-arginine and L-lysine degrading enzymes and their formulations, which have been successfully used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 160 publications
0
22
0
1
Order By: Relevance
“…The metabolic differences between normal cells and tumor cells provide opportunities for developing novel therapeutic approaches for cancer [1,2]. Normal cells are relatively resistant to the restriction of exogenous amino acids, whereas depletion of select amino acids in cancer cells inhibits cell cycle progression, induces cell death in vitro and suppresses tumor growth in vivo [3][4][5][6]. Depletion of amino acids in tumor cells can be achieved by dietary amino acid restriction [7,8] or by employing amino acid-degrading enzymes as therapeutic drugs [5,6,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic differences between normal cells and tumor cells provide opportunities for developing novel therapeutic approaches for cancer [1,2]. Normal cells are relatively resistant to the restriction of exogenous amino acids, whereas depletion of select amino acids in cancer cells inhibits cell cycle progression, induces cell death in vitro and suppresses tumor growth in vivo [3][4][5][6]. Depletion of amino acids in tumor cells can be achieved by dietary amino acid restriction [7,8] or by employing amino acid-degrading enzymes as therapeutic drugs [5,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Normal cells are relatively resistant to the restriction of exogenous amino acids, whereas depletion of select amino acids in cancer cells inhibits cell cycle progression, induces cell death in vitro and suppresses tumor growth in vivo [3][4][5][6]. Depletion of amino acids in tumor cells can be achieved by dietary amino acid restriction [7,8] or by employing amino acid-degrading enzymes as therapeutic drugs [5,6,9]. A number of amino acid-degrading enzymes have been developed over the past decade to deplete specific amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…L-ASNases have been identified in mammals, birds, plants, fungi, and a wide range of bacteria [ 3 , 4 ]. To date, dozens of microbial sources of L-ASNases have been revealed, though not all of them demonstrated cytotoxicity against leukemic cells or tumor inhibitory effects [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the side effect pattern of the enzymes is unique, which is significant for drug combinational therapy. Lastly, there exist key synthetases as biomarkers to forecast the therapeutic effect (Timosenko et al, 2017;Pokrovsky et al, 2019). Clinical trials of amino acid-degrading enzymes have shown that enzyme treatment is a safe and effective therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%